Engineering d‐p Orbital Hybridization in Single‐Atom Metal‐Embedded Three‐Dimensional Electrodes for Li–S Batteries (Adv. Mater. 44/2021). Issue 44 (1st November 2021) - Han, Zhiyuan; Zhao, Shiyong; Xiao, Jiewen; Zhong, Xiongwei; Sheng, Jinzhi; Lv, Wei; Zhang, Qianfan; Zhou, Guangmin; Cheng, Hui‐Ming
Abstract : Lithium–Sulfur Batteries A descriptor, the d–p hybridization state between singleatom metal catalysts (SACs) and sulfur species, to guide the design of SACs for Li–S batteries, is proposed by Shiyong Zhao, Qianfan Zhang, Guangmin Zhou, Hui‐Ming Cheng, and co‐workers in article number 2105947 . The large‐sized and flexible 3D electrodes with optimized SACs achieve high specific energy with low catalyst loading and high sulfur loading. The good mechanical stability for bending also shows potential for fabricating bendable/foldable Li–S batteries.